Selective mode excitation in SCM-OCDMA - Kabbour, Aliaa Mamoun; Amphawan, Angela; Fadhil, Hilal A.; Aljunid, Syed A (2013)
A six-channel 2.4GHz subcarrier multiplexing - optical code division multiple access (SCM-OCDMA) system in conjunction with the selective excitation of LP01 and LP02 modes is presented for a multimode fiber Local Area Network. Simulation results demonstrate that mode selectivity increases the bandwidth-distance product and improves the BER performance of the channel.